2017
DOI: 10.1200/jco.2016.68.8283
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of and Trends in High-Intensity End-of-Life Care Among Children With Cancer: A Population-Based Study Using Health Services Data

Abstract: Purpose Children with cancer often receive high-intensity (HI) medical care at the end-of-life (EOL). Previous studies have been limited to single centers or lacked detailed clinical data. We determined predictors of and trends in HI-EOL care by linking population-based clinical and health-services databases. Methods A retrospective decedent cohort of patients with childhood cancer who died between 2000 and 2012 in Ontario, Canada, was assembled using a provincial cancer registry and linked to population-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
108
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(123 citation statements)
references
References 39 publications
14
108
1
Order By: Relevance
“…We found no statistical evidence of a decrease in HI‐EOL or MI‐EOL care over time. This finding is in line with other countries in which no change or even an increase has been reported. Several explanations may account for the absence of a decrease, despite recent palliative policies for children in France.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found no statistical evidence of a decrease in HI‐EOL or MI‐EOL care over time. This finding is in line with other countries in which no change or even an increase has been reported. Several explanations may account for the absence of a decrease, despite recent palliative policies for children in France.…”
Section: Discussionsupporting
confidence: 92%
“…The exclusion of deaths that occur at home can overestimate HI‐ and MI‐EOL in our study. HI‐EOL would potentially be closer (approximately 51%) to the Canadian findings of Kassam et al if we hypothesize that the 20% of children, adolescents, and young adults who died of cancer at home in France (according to the French national death registry, Cépi‐DC) did not experience HI‐EOL. It is likely, however, that the true HI‐EOL value lies between these 2 bounds (51%‐61%).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…With the improvements in medical therapy for pediatric oncology patients, children now survive for longer periods and require extended PC, making pediatric PC an increasingly important area of research . Recent studies have investigated related ethical issues: how and when children should be involved in decision‐making and what disparities exist in PC access . Moreover, various studies have demonstrated PC for children with cancer is initiated late in the illness trajectory, indicating a discrepancy between the normative recommendation for early integration and referral practices in pediatric oncology.…”
Section: Introductionmentioning
confidence: 99%
“…In a large retrospective study 53 of 815 children with cancer, those who died after 2004 were more likely to have been in an intensive care unit, mechanically ventilated, or to have died in the hospital than those who died between 2000 and 2004. Taken together, these experiences underscore the need to understand, standardise, and integrate evolving PPC roles and services in paediatric oncology care.…”
Section: Current Era Of Ppc Oncology Research (2010 To Present)mentioning
confidence: 99%